The pity of war - Ferguson, Niall (Basic Books, 1999)
"In The Pity of War, Niall Ferguson explodes the myths of 1914-18. He argues that the fatal conflict between Britain and Germany was far from inevitable. It was Britain's declaration of war that needlessly turned a continental conflict into a world war, and it was Britain's economic mismanagement and military inferiority that necessitated American involvement, forever altering the global balance of power." "Ferguson vividly brings back to life one of the seminal catastrophes of the century, not through a dry citation of chronological chapter and verse, but through a series of chapters that answer the key questions: Why did the war start? Why did it continue? And why did it stop? How did the Germans manage to kill more soldiers than they lost but still end up defeated in November 1918? Above all, why did men fight?"--Jacket.